Paulicians Between the Dogme and the Legend - Tsibranska–Kostova, Mariyana (Studia Ceranea, 2017)
The paper compares how Paulicians were described in different types of medieval Slavonic sources by using the approach of the linguistic and culturological conceptualization of the alterity. By means of linguistic analysis, it tries to reach some essential dogmatic issues in the Paulician doctrine, and to focalize on the perception models towards Paulicians with their tangible semantic codes according to the specificities of the medieval world view. The two chosen texts the analysis is based on, are the legendary Bulgarian narrative Sermon about how the Paulicians have been conceived, and the Slavonic translation of 24th title of Panoplia Dogmatica by Euthymius Zigabenus. The analysis is followed by an English translation of the Sermon (insofar known in 8 copies), and a partial edition of the Slavonic translation of Zigabenus’s work upon the unique copy from the manuscript BAR 296, Library of the Romanian Academy of Sciences in Bucharest, dated between 1410–1420. The text account from the Slavonic manuscript is published for the first time, giving supplementary details about the overall Slavonic translation.